ENCAPSULATION OF VITAMIN AEVIT OIL SOLUTION WITH β-CYCLODEXTRIN - A. Iskineyeva; A. Mustafayeva; G. Zamaratskaya; A. Sarsenbekova; S. Fazylov; M. Burkeev; O. Nurkenov; T. Seilkhanov; R. Bakirova (Academic Journal of Physical and Chemical Sciences, 2021)
The present work aimed at encapsulation of fat-soluble vitamin Aevit (vitamins A and E, oil) with β-cyclodextrin. Inclusion complex of vitamins A and E with β-cyclodextrin was prepared in an aqueous alcohol medium by ultrasonic treatment. The surface morphology of the resulting clathrate inclusion complexes was described using a scanning electron microscope. The results of thermographic measurements on a differential scanning calorimeter are presented. The spectral properties of the inclusion complex are characterized by 1 H and 13C NMR spectroscopy data. The experimental results confirmed the existence of a complex of inclusion of β-cyclodextrin with vitamin Aevit (2:1). The activation energy of the thermooxidation destruction reaction of the clathrate complex β-cyclodextrin:vitamin Aevit was calculated, kinetic parameters of thermal destruction of clathrate were determined. These parameters were determined based on the Freeman-Carroll, Sharpe-Wentworth, Ahar and Coates-Redfern methods. The use of the above models made it possible to graphically establish the thermodynamic parameters of the thermal decomposition of β-cyclodextrin and its clathrate with vitamin. The data of thermographic measurements on a differential scanning calorimeter showed that the thermal destruction of the Aevite clathrate with β-cyclodextrin begins with the removal of water molecules from the β-cyclodextrin cavity, then the “guest” substance and the cyclic oligosaccharide are destroyed.